INFORMATION FOR AUTHORS –PHARMACOGNOSY REVIEWS (PHCOG REV.) (An official publication of Phcog.Net) - B.G., SHIVANANDA (Pharmacognosy Reviews)
The Pharmacognosy Reviews PHCOG REV. (ISSN: 0973- 7847) (An Official Publication of Phcog.Net; To be Indexed in Index Copernicus and other databases) A second publication series of Phcog.Net comprises contribution on every aspect of medicinal plant research and is aimed at documenting the vast and rich resource the nature has provided us with. PHCOG REV. consists of following Reviews Articles, Invited Articles, Clinical reports, Plant reviews, Review Articles, Short Reviews, General Articles. PHCOG REV. welcome contributions and Review Articles that describe investigations, clinical reports, methods, techniques and applications of all forms related to medicinal plant research and that are of immediate interest to users in industry, academia, and government. All contribution to Phcog Rev are reviewed editorially with the understanding that they have not been published previously and are not under consideration for publication elsewhere. Author/s is/are responsible for all statements made in their work and obtaining necessary permission to republish any previously published illustrations and/or other relevant materials. All contributions and manuscripts are subjected to peer review (Editorial, Phcog Rev Volume 1 Issue 1) and copyediting process.